The Potential of Murraya koenigii as a PfAp4AH Inhibitor for Malaria Drug Development - Inda Setyawati; Assifah Eryandini; Nadine Rudiyana; Laksmi Ambarsari; I. Made Artika (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Murraya koenigii, a medicinal plant from the Rutaceae family, is traditionally used as a flavoring agent and is known for its bioactive carbazole alkaloids. Native to the Indo-Malaysian region, China, Sri Lanka, and New Caledonia, this plant has shown potential for therapeutic applications, including antimalarial activity. Malaria, particularly caused by Plasmodium falciparum, remains a significant global health challenge due to rising drug resistance. PfAp4AH, an enzyme involved in diadenosine tetraphosphate (Ap4A) metabolism, has emerged as a promising target for novel antimalarial drugs. This study employed computational approaches—binding site prediction and virtual screening through molecular docking—to identify potential PfAp4AH inhibitors from 156 carbazole alkaloids derived from M. koenigii. Ten compounds demonstrated stronger binding affinities than ATP, with compound 1 showing the highest inhibitory potential through strong and diverse interactions with key residues Tyr87, His43, Pro133, and Leu136. These findings underscore the importance of specific ligand–residue interactions in determining binding strength. The identified compounds, especially compound 1, present promising leads for further experimental validation. While initial bioactivity and toxicity profiles are favorable, comprehensive bioavailability and toxicological evaluations are needed to advance these compounds as antimalarial drug candidates.